(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of digital transformation in enhancing the efficiency and effectiveness of educational administration in a sample of secondary schools in Al-Zawiya. It examined four dimensions of digital transformation: digital infrastructure, digital human resources, e-management, and digital culture. The study adopted the descriptive-analytical method and was applied to a sample of 90 participants from three secondary schools. The findings showed that the level of digital transformation was moderate and that digital transformation and its dimensions had a positive and statistically significant effect on the efficiency and effectiveness of educational administration.